KARAKTERISTIK ORGANOLEPTIK DAN NILAI GIZI BISKUIT SORGUM KACANG MERAH - Atmadja, Taufiq (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
Healthy and nutritious snacks are essential for the development of toddlers, especially those aged 1 to 5 years. One of the snack innovations is biscuits made from a combination of sorghum flour and red beans. The use of sorghum and kidney beans is expected to bring new innovations in providing nutrition for toddlers. In Indonesia, biscuits for children are generally still made from wheat flour, so product development using local food ingredients is needed. The combination of sorghum flour and red bean flour biscuits is expected to be a side dish in fulfilling nutrition and supporting the growth and development of children under five. The ingredients used were sorghum flour, kidney beans, wheat flour, cornstarch, egg yolk, margarine, powdered sugar, and milk powder. The biscuit processing method in this study contained two dough mixtures. Organoleptic test results showed that the best biscuit formulation was formula F1. F1 with the addition of wheat flour, shorghum flour, and red bean flour as much as 50 grams, 30 grams, and 10 grams, respectively. The organoleptic assessment of formula F1 obtained a score of 4.93 for the color aspect, 3.83 for the taste aspect, 4.1 for the aroma aspect, and 4.6 for the texture aspect. The results of nutritional analysis showed the moisture content of formula F1 was 6.475%, ash content was 2.36%, biscuit fat content reached 25.1%, biscuit protein content was 13.085%, and 52.98% for carbohydrate content